Electrochemical deposition of copper on zinc and its alloys - Kuznetsov, Boris V. (Journal of the Belarusian State University. Chemistry, 2022)
A new electrolyte composition and deposition conditions of quality (light, densely packed, homogeneous) copper coatings on zinc and its alloys were found. It was established that the electrochemical deposition of copper is possible from an alkaline solution containing propylene glycol. It was shown that the adding of hydroxyethylidene diphosphonic acid in the solution stabilises the electrolyte during operation and storage. The addition of morpholine provided deposition of quality copper coatings on zinc and its alloys in a wide range of current densities.